2017
DOI: 10.7717/peerj.3613
|View full text |Cite
|
Sign up to set email alerts
|

Plantar pressure distribution of ostrich during locomotion on loose sand and solid ground

Abstract: BackgroundThe ostrich is a cursorial bird with extraordinary speed and endurance, especially in the desert, and thus is an ideal large-scale animal model for mechanic study of locomotion on granular substrate.MethodsThe plantar pressure distributions of ostriches walking/running on loose sand/solid ground were recorded using a dynamic pressure plate.ResultsThe center of pressure (COP) on loose sand mostly originated from the middle of the 3rd toe, which differed from the J-shaped COP trajectory on solid ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Rather than being perfect molds of static feet, track morphologies arise through the dynamic interplay of pedal anatomy, step kinematics, and substrate properties [5][6][7][8][9][10]. Ground-dwelling birds have proven to be excellent models for experimentally studying these interactions [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Rather than being perfect molds of static feet, track morphologies arise through the dynamic interplay of pedal anatomy, step kinematics, and substrate properties [5][6][7][8][9][10]. Ground-dwelling birds have proven to be excellent models for experimentally studying these interactions [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Adult ostriches weigh between 80 and 200 kg. The load is mainly concentrated on the 3rd toe, with an area of 90 cm 2 [15,16,25]. Stress distribution was relatively uniform and there was no stress concentration area.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al and Schaller et al studied the ostrich plantar pressure distribution during the ostrich walked or ran gait through the dynamic pressure plate. The results showed that the 4th toe mainly played an auxiliary balance, and the plantar load was concentrated beneth the 3rd toe [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…(Brand et al, 2018;Cooper, 2000). All ostrich species have high adaptive properties; the survival rate of young and adult birds is at the level of 75-85% (Zhang et al, 2017). Now conditions have been created for the import of live ostriches from Europe, Africa and Australia.…”
Section: Introductionmentioning
confidence: 99%